Theoretical and experimental approaches of liquid entry pressure determination in membrane distillation processes - Rácz, Gábor; Kerker, Steffen; Kovács, Zoltán; Vatai, Gyula; Ebrahimi, Mehrdad; Czermak, Peter (My University, 2014)
Membrane distillation (MD) is a thermally driven separation process that employs a hydrophobic membrane as a barrier for the liquid phase, allowing only vapor phase to pass through the membrane pores. Wetting of membrane pores by liquid streams (i.e. the loss of hydrophobic characteristics of membranes) is a crucial issue in MD treatment. This paper is organized into two parts. The first part provides an overview of the theoretical background of wetting phenomenon and guides the reader through the experimental techniques presented in the literature for determining liquid entry pressure (LEP) of MD membranes. In the second part, we provide experimentally measured data on LEP values of some commercially available hollow-fiber and flat-sheet membranes tested in our lab using different MD configurations. The LEP[subscript w] value of the MD 020 CP 2N hollow-fiber membrane (Microdyn-Nadir GmbH, Wiesbaden, Germany) made of PP is found to be 0.97 bar using direct-contact membrane distillation (DCMD) configuration. The LEP[subscript w] value of the DuraporeTM GVPH flat sheet membrane (Merck Millipore Inc., Billerica, USA) made of PVDF is found to be 2.37±0.025 bar using static measurement technique and 1.90 bar using vacuum MD configuration. We also show that wetted membranes can be successfully regenerated by soaking them in ethanol and removing ethanol with evaporation at elevated temperatures. A novel concept of regeneration procedures applying vacuum have developed and have been proved to be effective for the tested flat sheet modules, however, failed on recovering the hydrophobic characteristics of the PP membrane in the hollow-fiber module.
Keywords: Liquid entry pressure; Membrane distillation; Microporous hydrophobic membrane; Hollow fiber module; Flat sheet module; Wetting phenomena; Regeneration of wetted pores